Plasma etching processes for interconnect realization in VLSI - Posseme, Nicolas (ISTE Press ; Elsevier Ltd, 2015)
This is the first of two books presenting the challenges and future prospects of plasma etching processes for microelectronics, reviewing the past, present and future issues of etching processes in order to improve the understanding of these issues through innovative solutions.